2008
DOI: 10.1128/cvi.00279-08
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Antibodies against Serogroup C Meningococci in England in the Postvaccination Era

Abstract: The United Kingdom introduced meningococcal serogroup C conjugate (MCC) vaccines in 1999, resulting in substantial declines in serogroup C disease and carriage. Here, we measured the age-specific prevalence of serum bactericidal antibodies (SBA) to Neisseria meningitidis serogroup C and immunoglobulin G (IgG) concentrations to serogroups A, C, W-135, and Y in 2,673 serum samples collected in England between 2000 and 2004. We compared the seroprevalence of SBA titers of >8 in the postvaccination era with result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 32 publications
6
44
0
Order By: Relevance
“…Seroprevalence studies of infants and adolescents have shown that the decline in effectiveness in infants paralleled the decline in SBA, while SBA titers in adolescents showed little evidence of a decline with time, mirroring the sustained high effectiveness in this age group (27,39). Our SBA data similarly indicate a fairly rapid fall in the proportion of children with SBA titers of Ն8 within the first 12 months after primary immunization, followed by relative stability (Table 1).…”
Section: Discussionsupporting
confidence: 56%
“…Seroprevalence studies of infants and adolescents have shown that the decline in effectiveness in infants paralleled the decline in SBA, while SBA titers in adolescents showed little evidence of a decline with time, mirroring the sustained high effectiveness in this age group (27,39). Our SBA data similarly indicate a fairly rapid fall in the proportion of children with SBA titers of Ն8 within the first 12 months after primary immunization, followed by relative stability (Table 1).…”
Section: Discussionsupporting
confidence: 56%
“…The data were first categorized into the same age-bands used in our two previous similarly designed surveys of samples taken prior to MCC introduction (in 1996 to 1999) and shortly after introduction of MCC (in 2000 to 2004) (21,23) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Field effectiveness of the initial 3-dose vaccination schedule (given at ages 2, 3, and 4 months) was shown to wane rapidly (22), and serological studies found that only 36% of children were still protected (defined as a serum bactericidal antibody [SBA] titer of Ն8, with rabbit complement) 18 months after infant vaccination (20,23). In 2006, the immunization schedule was adjusted such that MCC vaccine is now given at ages 3, 4, and 12 months.…”
mentioning
confidence: 99%
“…Loss of vaccine effectiveness and the apparition of vaccine failures have been associated to an inadequate maintenance of circulating antibodies [7][8][9]. The effect of immaturity of the immune system in infants [10,11] to maintain the antibody levels in time has been widely studied in seroprevalence studies [9,[12][13][14][15][16][17]. In line with this, in our previous nationwide study evaluating vaccine effectiveness after 13 years since the conjugate vaccine introduction, we found 63.97% of vaccine failures in those vaccinated before the year of age (2-3 doses), 32.08% in those vaccinated between 1 and 11 years (1 dose) and 3.88% in those vaccinated between 12-19 years (1 dose) [18].…”
Section: Introductionmentioning
confidence: 99%